Sosialisasi dan Workshop Robotika untuk Skala Pelajar - Ida Rachmaniar Sahali; Muh. Bachtiar Nappu; Muh Anshar; Dewiani -; A. Ejah Umraeni Salam; Intan Sari Areni; Azran Budi Arief; Andani Achmad; Hasniaty -; Rhiza S. Sadjad; Merna Baharuddin (Faculty of Engineering UNHAS, 2020)
The field of robotics is of great interest to students. This can be seen from the enthusiasm of SMP IT Ikhtiar students who want to take part in socialization activities and robotics workshops held by the Social Research Group, Cognitive Robotics and Advanced Artificial Intelligent Research Center, Electrical Engineering UNHAS. This activity provides knowledge about the basics and current applications of the field of Robotics and teaches students to be able to assemble simple robots using easily obtained electronic materials and components. The workshop was held semi-online where there were 6 (six) people consisting of teacher and student representatives who attended activities in the laboratory and there were also more than 50 students who attended virtually via teleconference. To be able to provide an understanding of robotics for students, it requires qualified external personnel who master the field of electrical engineering, especially robotics. From the comparison of the pre-test and post-test results before and after participating in the activity, it was obtained a significant increase in the knowledge of the students. In addition, students also succeeded in assembling robots using the materials and components that had been provided. As materials for the sustainability of the program, the robots assembled by students were then given to them to be studied again.